La flexibilidad inflexible: estudios de caso de plantas maquiladoras electrónicas en el norte de México - de la O-Martínez, María Eugenia (Papeles de Población, 2021)
One of the most controversial assumptions about «productive modernization» in the nineties is the presence of a new type of managerial-worker relationship —if this assumption is true, it will entail a radical change in the work place—. The objective of this article is to measure the effects of «productive modernization» in the «maquiladora» electronic industry. This sector was chosen because of its propensity to technological and organizational change due to its links with the international markets and corporations. With four case studies, it was possible to identify how complex the modernization and flexibility of the labor force can be for these industries. These processes, due in part to technological and organizational change, are the combination of manual dexterity versus the new conceptions of labor force usage, longer workdays with more responsibilities and renewed forms of control and subordination.